The effect of short period high-intensity circuit training-modified FIFA 11+ program on physical fitness among young football players - Zein, M. I.; Saryono, S.; Laily, I.; Garcia-Jimenez, J. V. (The Journal of Sports Medicine and Physical Fitness, 2020)
BACKGROUND: Studies showed that FIFA 11+, the football injury prevention program, can improve physical fitness components through resistance and neuromuscular exercise. Currently, resistance training using High Intensity Circuit Training (HICT) is considered beneficial in increasing physical fitness component, including maintaining cardiopulmonary fitness. The purpose of this study was to evaluate the effect of HICT modified- FIFA 11+ training on the physical fitness components and cardiovascular (CV) training intensity of young football players. METHODS: Thirty-nine football players were recruited by purposive random sampling to the football academies in Yogyakarta, Indonesia. The players were randomized into two groups; 20 players were in the experiment (EXP) group and 19 players were in the control (CON) group. The EXP group performed HICT-modified FIFA 11+ exercise and the CON group performed standard FIFA 11+. HICT modification was performed in the EXP group only in part 2 of FIFA 11+ (strength, power, and balance training) while the other parts were regular. Both groups performed the intervention 3 times per week for 4 weeks. All players completed a pre- and post-intervention physical fitness tests comprising the core strength (plank test), leg strength (leg dynamometer) and agility (Illinois test). Heart rate (HR) was monitored in both groups while exercise was being implemented to measure the CV training intensity. Changes in performance (pre- versus post-intervention) of each group were analyzed using paired t-test and Wilcoxon test. Statistical significance was set to P<0.05. Twelve players dropped out in this research. RESULTS: This study showed that core strength increased significantly in both groups (P=0.00). The EXP group had higher CV training intensity (HR max 91%; mean HR 74%) than the CON group (HR max 90%; mean HR 66%). CONCLUSIONS: Results suggest that HICT modified FIFA 11+ can be implemented as an alternative program to increase the physical fitness components and also CV training intensity among young football players.